Macrozoobenthos diversity in the waters of Krueng Pasee River - Rinaldi, Rinaldi; Yanto, Nopri; Muktitama, Asih Makarti; Nugrahawati, Anis; Sari, Cut Rozana; Khalil, Munawwar (Acta Aquatica: Aquatic Sciences Journal, 2025)
Macrozobenthos is a sensitive water biota to changing water quality, it can give you an idea of the water conditions. The research was done by subtracting samples from the waters of the Pasee River and being analyzed in the lab. The abundance of macrozoobenthos on the various pasee rivers ranged between 140 ind / m2, the diversity index ranged from 2,039, the evenness index from 0,928, and the dominant index from 0.503. Of that value, it can be said that the water condition of the river is still good. Keyword: Abundance; Dominant; Evenness; Krueng Pasee; Macrozobenthos